Competition, imitation, and R&D productivity in a growth model with sector-specific patent protection - Malte Mosel (Verein für Socialpolitik, 2010)
Recent empirical studies find vast industry differences in how patent protection influences innovation and growth. An optimization of aggregate growth, therefore, implies the need for a flexible patent regime responding to each industrys characteristics. In practice, sector-specific modifications of patent strength already exist but lack theoretical foundation. This paper intends to make up for this neglect by scrutinizing in what direction industry characteristics influence optimal patent strength. It is found that patents ought to be weaker, the more intense competition, the higher R&D productivity, and the more intricate reverse engineering are. Unlike similar step-by-step innovation models of economic growth, the model assumes Cournot competition and introduces an empirically substantiated measure of sector differences in the ability to catch up with the technological leader. It is found that for most empirically plausible cases the familiar inverted-U relation between patent length and growth carries over to the Cournot set-up.
Keywords: O31; O34; L16; 330; competition; imitation; innovation; Schumpeterian growth; sector-specific patent protection; Supplementary Protection Certificates